Conceptualizing Policy on Underwater Cultural Heritage Towards Legal Protection and Ecotourism Promotion in Karimun Jawa, Indonesia - Dhiana Puspitawati; Moh. Fadli; Mustafa Lutfi; Syahriza Alkhoir Anggoro; Mohd Hazmi Mohd Rusli (Faculty of Law, Universitas Negeri Semarang, 2024)
Journal of Indonesian Legal Studies Volume 8 Issue 2 (2023), pp. 633-662